Daytime CO2 urban surface fluxes from airborne measurements, eddy-covariance observations and emissions inventory in Greater London. (January 2015) - Font, A.; Grimmond, C.S.B.; Kotthaus, S.; Morguí, J.-A.; Stockdale, C.; O'Connor, E.; Priestman, M.; Barratt, B.
Abstract: Airborne measurements within the urban mixing layer (360 m) over Greater London are used to quantify CO2 emissions at the meso-scale. Daytime CO2 fluxes, calculated by the Integrative Mass Boundary Layer (IMBL) method, ranged from 46 to 104 μmol CO2  m −2  s −1 for four days in October 2011. The day-to-day variability of IMBL fluxes is at the same order of magnitude as for surface eddy-covariance fluxes observed in central London. Compared to fluxes derived from emissions inventory, the IMBL method gives both lower (by −37%) and higher (by 19%) estimates. The sources of uncertainty of applying the IMBL method in urban areas are discussed and guidance for future studies is given. Highlights: CO2 was measured by aircraft in London within the urban mixing layer (360 m). Meso-scale urban emissions were estimated using aircraft observations. Airborne-fluxes within −37% and 20% of emissions from inventory. Airborne-fluxes within the range of eddy-covariance observations in central London. Abstract : CO2 airborne-derived fluxes by Boundary Layer Mass balance are an independent measure of meso-scale urban fluxes complementing urban eddy-covariance fluxes and emissions inventory.